Evaluation of level of service (LOS) on routes of smart bus in Kajang, Selangor - Mat Shukri, Nur Shazreena; Ponrahono, Zakiah; Sunoto @ Hj. Faisal, Yakin Nur; Wan Ghazali, Wan Noratikah Wahidah (Malaysian Institute of Planners, 2020)
Level of service (LOS) is a method used for the development of transportation infrastructure designations based on a specific analysis. The concept of LOS lies on the importance of an assessment of roadway operational performance services for the improvement of bus service delivery. A high performance of bus service delivery could relatively influence the satisfaction level of its users. This study assesses the LOS of three main designated routes of SMART buses in Kajang Selangor (KJ01, KJ02, and KJ03). TheSMART buses are free buses provided under a free transit programme which aims to encourage people to use public transportation. An on-board survey and inventory observation were employed to collect the data. Findings indicate that KJ01, KJ02, and KJ03 fall under the category of LOS D considering the attributes of service frequency, service hours, passenger load/thresholds, and speed of bus. The discovery may serve as a useful guidance for the development of a comprehensive plan for LOS to be coordinated in improving the service quality of bus transportation